THE USE OF DEBATE TECHNIQUE FOR THE IMPROVEMENT OF ENGLISH SPEAKING SKILL OF THE SECOND GRADE STUDENTS OF TOURISM DEPARTMENT OF SMK NEGERI 1 KUPANG IN THE ACADEMIC YEAR 2014/2015 - Hendrik, Marion Derissilfia Grace (JURNAL TRITON PENDIDIKAN, 2016)
This study is based on the important of speaking skill. Speaking is important to be learnt because speaking is the way to communicate with other people in order to deliver opinion and express idea, but in fact the students’ ability in speaking English is very low. There are some elements of speaking such as vocabulary, pronunciation, grammar, fluency and comprehension that must be mastered by students in order to be a good English speaker. In this research, the researcher used debate technique to improve students’ speaking skill. The main objective of this study is to describe the use of debate technique in improving speaking skill and to identify the students’ speaking skill improvement after being taught by using debate technique. This study is classroom action research that was done in two cycles. The data collection was done by using observation, test and questionnaire. The data from the observation that had been taken from every cycle analyzed descriptively and the data from test was analyzed in the form of numbers and descriptively, while the data from questionnaire also analyzed descriptively. The participant of this study was 36 students in class XI UPW 1. The result of this study shows that using debate technique can improve students’ speaking skill. This is proven by students’ test score that improved in every cycle. In the first cycle, the students’ average score was 2,1 and in the second cycle students got 3,3. Debate is an appropriate technique used to improve students’ speaking skill. The result of this study is hopefully can be used as an information for English teachers in teaching speaking.